Depletion of Arginine by Recombinant Arginine Deiminase Induces nNOS-Activated Neurotoxicity in Neuroblastoma Cells. (14th July 2014) - Lin, Shan-Erh; Wu, Fe-Lin Lin; Wei, Ming-Feng; Shen, Li-Jiuan
Abstract : The abnormal regulation of inducible nitric oxide synthase (iNOS) and neuronal nitric oxide synthase (nNOS) is associated with neurodegenerative disorders. Recombinant arginine deiminase (rADI) is a selective NO modulator of iNOS and eNOS in endothelial cells, and it also exhibits neuroprotective activity in an iNOS-induced neuron-microglia coculture system. However, the effect of rADI on nNOS remains unknown. Addressing this issue is important for evaluating the potential application of rADI in neurodegenerative diseases. SH-SY5Y cells were treated with N -methyl-D-aspartic acid (NMDA) to activate nNOS. NMDA increased NO production by 39.7 ± 3.9% via nNOS under arginine-containing conditions, but there was no significant increase in both arginine-free and rADI pretreated arginine-containing (citrulline) buffer. Subsequently, neither NMDA nor rADI alone caused cytotoxicity, whereas cotreatment with NMDA and rADI resulted in dissipation of the cell mitochondrial membrane potential and decreased cell viability. The mechanism of rADI cytotoxicity in the presence of NMDA is caused by the inhibition of NO production via nNOS mediated by the NMDA receptor, which was abolished when extracellular arginine was absent, even in the presence of citrulline. rADI not only reduced NO production but also caused cellular toxicity in nNOS-activated SH-SY5Y cells, suggesting a dual role for rADI in NOS-mediated neurotoxicity.